Sports performance and the brain - Nakata, H. (Sports Performance, 2015)
The relationship between sports performance and the brain was examined based on data obtained using non-invasive neurophysiological and neuroimaging methods. Background brain electrical activity has been recorded by electroencephalography (EEG) during sports performance. EEG has previously been used to investigate aiming sports such as billiards, darts, shooting, and golf. This review mainly describes EEG data obtained during golf putting by experts and non-experts. A focus was placed on neural substrates in the golfers` brains as a model of neural plasticity based on studies utilizing functional magnetic resonance imaging (fMRI) and structural MRI. Several problems that should be addressed in future studies in this field were also discussed.